Объяснение:
1) SO2 + 2KOH = K2SO3 + H2O
SO2 + 2K(+) + 2OH(-) = 2K(+) + SO3(2-) + H2O
SO2 + 2OH(-)= SO3(2-) + H2O
2) Cu(OH)2 + H2SO4 = CuSO4 + 2H2O
Cu(OH)2 + 2H(+) + SO4(2-) = Cu(2+) + SO4(2-) + 2H2O
Cu(OH)2 + 2H(+) = Cu(2+) + 2H2O
3) Zn(OH)2 + 2HCl = ZnCl2 + 2H2O
Zn(OH)2 + 2H(+) + 2Cl(-) = Zn(2+) + 2Cl(-) + 2H2O
Zn(OH)2 + 2H(+) = Zn(2+) + 2H2O
4) Ba(OH)2 + H2SO4 = BaSO4↓ + 2H2O
Ba(2+) + 2OH(-) + 2H(+) + SO4(2-) = BaSO4↓ + 2H2O
5) Ba(OH)2 + 2HNO3 = Ba(NO3)2 + 2H2O
Ba(2+) + 2OH(-) + 2H(+) + 2NO3(-) = Ba(2+) + 2NO3(-) + 2H2O
OH(-) + H(+) = H2O
Fe + 2HBr = FeBr2 + H2
Fe(0) + 2H(+) + 2Br(-) = Fe(2+) + 2Br(-) + H2(0)
Fe(0) + 2H(+) = Fe(2+) + H2(0)
Zn + CuSO4 = ZnSO4 + Cu
Zn(0) + Cu(2+) + SO4(2-) = Zn(2+) + SO4(2-) + Cu
Zn(0) + Cu(2+) = Zn(+2) + Cu(0)
1)Ch4+cl2=ch3cl+hcl
2)ch3cl+na-ch3-ch3+nacl
3)ch3-ch3(t)=ch2=ch2+h2
4)ch2=ch2+hcl=ch2cl-ch3
5)ch2-ch3+cl2=ch2cl-ch2cl+hcl Этан ch3-ch3(t)=ch2=ch2+h2(этилен)
|
cl ch2=ch2+3o2=2co2+2h2o(углекислый газ)
ch2=ch2+hoh=ch2-ch2
|
oh